# -(2x-6)+10x=-5x-3(-7x-7)

## Simple and best practice solution for -(2x-6)+10x=-5x-3(-7x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -(2x-6)+10x=-5x-3(-7x-7) equation:

-(2x-6)+10x=-5x-3(-7x-7)
We move all terms to the left:
-(2x-6)+10x-(-5x-3(-7x-7))=0
We add all the numbers together, and all the variables
10x-(2x-6)-(-5x-3(-7x-7))=0
We get rid of parentheses
10x-2x-(-5x-3(-7x-7))+6=0

We calculate terms in parentheses: -(-5x-3(-7x-7)), so:
-5x-3(-7x-7)
We multiply parentheses
-5x+21x+21
We add all the numbers together, and all the variables
16x+21
Back to the equation:
-(16x+21)

We add all the numbers together, and all the variables
8x-(16x+21)+6=0
We get rid of parentheses
8x-16x-21+6=0
We add all the numbers together, and all the variables
-8x-15=0
We move all terms containing x to the left, all other terms to the right
-8x=15
x=15/-8
x=-1+7/8

`